Physiotherapy techniques used in injury treatment: A systematic review of tennis elbow - Simplicio, Claudio Lopes; Purita, Joseph; Murrell, William; Santos, Gabriel Silva; dos Santos, Rafael Gonzales; Lana, JosÃ© FÃ¡bio Santos Duarte (Universitas Tanjungpura, 2024)
Background and Study Aim. This review provides a comprehensive analysis of the physiotherapy methods used to treat tennis elbow, emphasizing the importance of understanding its pathophysiology and etiology to inform effective treatment strategies.Material and Methods. This review explores a range of physiotherapy interventions, including manual therapies that alleviate pain and improve joint function. Techniques such as joint mobilization, soft tissue massage, and myofascial release are highlighted. Additionally, exercise rehabilitation plays a key role, with individualized exercise programs designed to strengthen weakened muscles and improve elbow biomechanics. The study utilized the Harzing Publish or Perish application for its literature search, sourcing relevant studies from Google Scholar and PubMed using keywords like